Penerapan Prinsip Pencemar Membayar (Polluters Pay Principle) Pada Kasus Tindak Pidana Kerusakan Lingkungan Dengan Dakwaan Delik Korupsi (Studi Kasus: Gubernur Sulawesi Tenggara) - Putri, Syifadilla Subagyo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the application of the Polluter Pays Principle in the case of Nur Alam, former Governor of Southeast Sulawesi, who was convicted of corruption related to mining permits that caused environmental damage. Using a normative juridical approach, this research analyzes Law No. 32 of 2009 and Ministerial Regulation No. 7 of 2014. The findings reveal that ecological losses resulting from corruption should be classified as state losses. However, Indonesia’s legal framework remains weak in integrating environmental aspects into corruption cases involving natural resources.